Engines of democracy : politics & policymaking in state legislatures - Rosenthal, Alan (CQ Press, 2009)
State legislators have often been in the shadow of their national counterparts, but they drive the processes of democracy.   Rosenthal brings together a lifetime of research and experience on state legislative politics into one eminently readable volume--a dynamic, inside view of the people involved, the politics that prevail, and the interest groups and lobbyists who advocate their causes. Building on earlier work with new data and recent interviews and observations, Rosenthal looks at the way representation works, Americans' critical view of their legislatures, the role of legislative leaders, the dynamics of executive-legislative relationships, as well as norms and ethics. Both a complement and contrast to the policymaking process on Capitol Hill, Engines of Democracy proves that no one gives insight into state legislators and their work the way Alan Rosenthal can.